Conception d’une grille d’observation de la résolution collaborative de problèmes (RCP) - Parent, Simon (Canadian Journal of Education/Revue canadienne de l'éducation, 2023)
Collaborative problem solving (CPS) has been the subject of many studies and reflections over the years. Given our realization that there are very few tools for studying CPS in an authentic context, we thought it would be relevant to propose one. This article presents the steps that led to the design of a CPS observation grid. Based on Strayer and Gauthier’s (1982) model, we present the process structured in three parts: the descriptive phase, the exploratory phase, and the systematic evaluation. This last phase, conducted with the help of a videography device, was carried out with 109 primary school students in three Quebec schools. Composed of three dimensions through which 15 indicators are distributed, this grid offers an interesting perspective on the qualitative and interpretative observation of the mobilization of CPS skills. This tool makes it possible to calculate frequencies, but also to interpret the behaviours associated with each of the indicators in order to formulate hypotheses or to allow school personnel to orient their interventions or teaching practices according to the needs of the students.